2008 IEEE MTT-S International Microwave Symposium Digest 2008
DOI: 10.1109/mwsym.2008.4633303
|View full text |Cite
|
Sign up to set email alerts
|

Miniature antenna for RF telemetry through ocular tissue

Abstract: In this study, we experiment with the feasibility of wireless telemetry using a miniature wireless system fully implanted within the eye. Of significant importance is the ability to transmit signals from miniature packaged systems without undue absorption of signals. Theoretical calculations found the attenuation through the eye to be -4.5 dB in the far field region, indicating that low power transmission systems can be implemented. Through the use of multilayer integrated Low Temperature Co-fired Ceramics (LT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 1 publication
1
6
0
Order By: Relevance
“…In an ex vivo study done in [2] using a similar LTCC board, the near-field result showed a 1.75-1.93-dB attenuation while at further distances the attenuation was about 5.89 dB. That data correlates well with the 1.3-2.45-dB attenuation we see at close distances and the 6.9-dB value at further distances.…”
Section: Data and Analysissupporting
confidence: 74%
See 2 more Smart Citations
“…In an ex vivo study done in [2] using a similar LTCC board, the near-field result showed a 1.75-1.93-dB attenuation while at further distances the attenuation was about 5.89 dB. That data correlates well with the 1.3-2.45-dB attenuation we see at close distances and the 6.9-dB value at further distances.…”
Section: Data and Analysissupporting
confidence: 74%
“…LTCC was chosen for its ease of fabrication, durability, high dielectric, and multilayer capabilities. The ex vivo results of one of our initial LTCC antenna designs is reported in [2]. We modified and optimized the design further for this study, resulting in the design shown in Fig.…”
Section: Antenna Designmentioning
confidence: 99%
See 1 more Smart Citation
“…The overall efficiency of wireless powering depends on the rectification efficiency for a given frequency of powering, input power delivered, resonance and impedance mismatch losses, antenna geometry, and tissue losses. The effective power available at the rectifier input depends on multi path losses (~1-10dB for a range of 1-100cm, assuming a two-ray ground reflection model), skin attenuation based on implant depth (~5dB for 1-3mm below the skin, ~30dB for a depth of 3-5cms), antenna efficiency and matching losses (~5-10dB depending on frequency, antenna size and topology) [5]- [6].…”
Section: Headstage Design Considerationsmentioning
confidence: 99%
“…This takes advantage of the maturity of stent technology and delivery procedures, as well as producing a novel, enabling platform for using stents as radiating antennas. Previous work has measured the tissue loss faced by transcutaneous telemetry for various antennas, but the use of stent‐based antennas implanted deep within the chest has not been characterized 18–20 . The data transfer technology can be applied in the future to other implantable devices designed to monitor blood pressure.…”
Section: Introductionmentioning
confidence: 99%